Modelos de crecimiento individual de especies de interés comercial de la Selva Paranaense = Individual growth models for commercial timber species of Paranaense Forest - Pinazo, Martin Alcides (2019)
Growth models are a key tool for sustainable forest management. The predictions of growth and yield obtained through models are necessary for effective timber logging, management planning, evaluation of the sustainability, strategic planning of resources and the formulation of policies. The present work explores the generation of individual tree level growth models for arboreal species of the Paranaense forest using the Lieberman and Lieberman and the Chapman Richards models. The models used in the present work, for their flexibility and simplicity, represent a solution to be considered in growth projections for the realization of the sustainable management of the Paranaense forest.